(untitled) (International Journal of Environmental Sciences, 2025)
This study investigates the strategic transition from conventional grey ammonia to green and blue ammonia technologies in Indonesia’s fertilizer industry, with the goal of aligning agricultural productivity with national net-zero emission targets by 2060. A mixed-methods approach was employed, integrating stakeholder analysis, Life Cycle Assessment (LCA), cost-benefit analysis (CBA), and scenario modeling. Data were gathered through 30 in-depth interviews with representatives from state-owned enterprises, private fertilizer firms, financial institutions, farmers, research institutions, and environmental NGOs. Quantitative analysis followed ISO 14040/44 LCA protocols and long-range policy simulations using LEAP and Vensim modeling tools. Green ammonia produced via renewable-powered electrolysis emerged as the most environmentally sustainable pathway, reducing CO₂-equivalent emissions by up to 94% compared to grey ammonia. Although capital-intensive, green ammonia becomes economically viable within 15 years under targeted subsidies and carbon pricing. Blue ammonia offers an intermediate solution but is limited by CCUS efficacy and fossil fuel dependency. Thematic analysis revealed five critical transition domains: technological feasibility, economic viability, environmental risk, policy alignment, and market acceptance. Scenario modeling demonstrated that only the full-scale adoption of green ammonia under an integrated sustainability framework achieves compliance with Indonesia’s NDC targets and generates long-term economic and social co-benefits. This study provides one of the first integrative assessments of sustainable ammonia transitions in Southeast Asia, combining stakeholder governance, environmental metrics, and macroeconomic modeling. The findings offer actionable insights for policymakers, industry leaders, and development partners aiming to decarbonize agricultural inputs while fostering rural resilience and green innovation.